The Valid and Reliable Semi-Quantitative Food Frequency Questionnaire among the Sleman Under Five Children - Yayuk Hartriyanti SKM, MKes; Nikita Dika Melindha SGz; Ratri Kusuma Wardani SGz; Aviria Ermamilia MGizi, RD; Septi Kurnia Lestari SGz, MMedSc (PH) (SAGE Publishing, 2023)
To examine macronutrient intake among under-five children, which is cost-effective, reliable, and validated by regional food choice and availability, we developed a new Semi Quantitative-Food Frequency Questionnaire (SQ-FFQ). We validated the Sleman Under Five Children SQ-FFQ (SUFS) compared to the 3-time 24-hour recalls (24HR) and conducted reliability tests between the first and second SUFS interviews. This study included 102 under-five children. All tests were conducted for the "12-35 months" and "36-59 months" groups. Compared to 24HR using Pearson's Correlation Coefficient, Spearman's Correlation Coefficient, Bland Altman plots, Cross Classification and Limits of Agreement (LOA), the SUFS was valid but significantly overestimated the macro-nutrient consumption. The reliability test results using the Interclass Correlation Coefficient and Cronbach's alpha showed moderate to good reliability (ICC and α ranged from .6 to .9), and a high correlation using Spearman's Correlation Coefficient (rho:.42-.89). The SUFS is valid compared to the 24HR and reliable for assessing macronutrient consumption for children under five.